Risk of local extinction and genetic diversity of Melipona quadrifasciata (Apidae: Meliponini) in a possible Northeastern limit of its distribution in Brazil - Araújo, Edilson D; Oliveira, Rosane Gomes; Calazans, Higor Cesar Meneses; França, Carina Caroline Silva; SANTOS, Valdson; Jain, Sona Arun; Batista, Marcus Vinícius Aragão; Nunes, Lorena Andrade; Ribeiro, Genésio Tamara (Sociobiology, 2016)
Rapid loss of genetic diversity among eusocial bees, and extinction of their local population has become a major world concern. Populations of M. quadrifasciata have increasingly declined due to predatory extractivism and destruction of their habitat. Knowledge of their local population could give insights on the strategies for monitoring and conservation of this species. In this study, initially, 14 colonies (140 workers) from the Northern limit of the Northeastern sandbank of the Atlantic Forest were analyzed employing geometric morphometrics techniques. Then the cytochrome b gene sequences and ISSR primers were utilized for molecular analysis. The results were compared with the results of 30 M. quadrifasciata colonies (300 workers) found in the semiarid Caatinga region. The morphometrics and the molecular analysis suggested the formation of disjunct populations between the studied geographical zones. All the 14 colonies analyzed from the river São Francisco region were found on the Southern margin of the river São Francisco and they all belonged to one single haplotype. No colonies were found on the Northern bank of the river. We suggest that the river São Francisco is an effective georgraphical barrier for the distribution of this species and propose an urgent need for the development of a conservation program for the population of M. quadrifasciata as it represents a unique haplotype in the region. Also their nesting habit exclusively in the diseased coconut trees which probably will be replaced by new trees, create the risk of population extinction due to the lack of nesting site.